A Numerate Film History? Cinemetrics Looks at Griffith, Griffith Looks at Cinemetrics - Mike Baxter | Daria Khitrova | Yuri Tsivian (Mise au Point)
The field of study we visit in this article is the history of editing. Specifically, we look at D.W. Griffith’s essay “Pace in the Movies” (1926) which says that specific scenes in films must be edited with specific shot lengths in mind. In a model movie cuts between shots must come with a wavelike frequency, Griffith insists, and offers his recipe as to the perfect wave curve within the duration of the film. Griffith’s post-analysis based on his experience as a director and editor has caused a controversy among modern-day film historians. Some use it as an argument in favor of numeric approaches to film style; others doubt whether it was Griffith who authored this idea, and if it was, whether Griffith meant what he meant.